The Influence of Social Media Marketing and Brand Image on Buyer's Decision: (Survey on Followers of Mixue Nganjuk’s Instagram Account) - Sumarsono, Anggoro Bekti; Hakimah, Ema Nurzainul (Universitas Nusantara PGRI Kediri, 2024)
Research aim: The purpose of this study is to determine and explain the significant influence between social media marketing and brand image, both partially and stimulantly on buyer decisions on followers of Mixue Nganjuk outlet Instagram account. Design/Methode/Approach: This study was conducted to analyze the influence of social media marketing and brand image on buyer decisions on followers of Mixue Nganjuk outlet Instagram account. This study used a quantitative approach with the population in this study all followers of the Instagram account @mixue.nganjuk which is the official social media account owned by Mixue Nganjuk. The sample was determined as many as 116 respondents taken using non-probability sampling techniques with purposive sampling. In this study using multiple linear regression to see how much influence the independent variable has on the dependent variable. Research Findings: The result of this study is that social media marketing and brand image have a significant effect on purchasing decisions on followers of Mixue Nganjuk outlet Instagram account. Theoretical contribution/Originality: Social media marketing can broaden the understanding of how social media as a digital marketing platform, delves deeper into the consumer's perspective in the brand image of a product to influence consumers in making purchasing decisions. Practitionel/Policy implication: This study provides practical implications for Mixue Nganjuk in improving brand image in the influence of purchasing decisions. Research limitation: This study discusses social media marketing and brand image as independent variables, and purchase decisions as dependent variables.